Listening Comprehension Problems: The Pre-Diploma Students’ Insights and Experiences - Abu Bakar, Azrina binti (University of Muhammadiyah Prof. DR. HAMKA, 2019)
Despite the fact that listening is one of the fundamental skills to develop in English language learning, most of the pre-diploma students at Universiti Teknologi Mara (UiTM) Cawangan Melaka often regard listening as a difficult skill to learn. However, little research has been conducted regarding the listening comprehension problems that they experienced in English class. This paper, thus investigates the pre-diploma students’ insights into English listening difficulties that they encountered in listening comprehension and explored numerous effective listening strategies to improve their English listening abilities. 80 pre-diploma students who took the Pre-Diploma English Language course were selected randomnly for the study. Data collections included 5-point Likert type questionnaire and semi-structured interviews. Results suggest that the main problems highlighted by most students are linked to the speed of speech, text length, vocabulary knowledge, and unfamiliar accents.